The Effectiveness of The Competitive Strategy "Social Coffee" Anak Panah Kopi Tembalang - Nurul Indriyani (Jurnal Manajemen Bisnis, 2022)
The rise of coffee consumption has now become a new culture among consumers. As reviewed by a study in Mix Magazine with the support of Toffin, which states that there are several factors for the growth of coffee shops in Indonesia, including the culture of hanging out while drinking coffee which is directly proportional to the increase in the coffee shop business margin which is quite high. In this case, the research was conducted on Anak Panah Kopi Tembalang, in particular on the use of the word "social coffee" as a marketing strategy. This research was conducted with qualitative research methods with participatory observation, documentation. There are 12 respondents including the supervisor of Anak Panah Kopi Tembalang, Head of Anak Panah Kopi Tembalang, and 10 customers of Anak Panah Kopi Tembalang with the indepth interview method. The results of this study found that customers indirectly interpreted "social coffee" as intended by management, with a note of various pro and con opinions so that it became a suggestion to improve several aspects for the managerial side to survive during intense competition with other competitors.